Fluorescence huminových kyselin 3D excitačně emisní metodou. - Mlčoch, Tomáš (Vysoké učení technické v Brně. Fakulta chemická, 2008)
Cílem této práce bylo změřit a popsat EEM spektra IHSS standardů huminových kyselin, půdních či lignitických huminových nebo fulvinových kyselin a humátů různého původu. Popsat odlišnosti v jejich fluorescenčních spektrech a určit přesnou polohu hlavních fluorescenčních píků. Dále nalézt optimální postup zpracování naměřených dat do formy 3D EEM spektrofluorogramů a u vzorků lignitických humátů prozkoumat závislost jejich relativní intenzity fluorescence na hodnotě pH.

The aim of the diploma thesis was measurement and characterization of EEM (excitation emisssion spectra) of IHSS humic acids standards and soil, lignite humic and fulvic acids and humates prepared from different sources. The aim was to follow the differences in their fluorescence spectra and to determine precise location of fluorescence peaks. Target of this work was to find the optimal way for exporting of scan data to the 3D EEM spectrofluorographs. The dependence of relative intensity of fluorescence on pH value was studied further.
Fluorescence spectroscopy of humic acids by excitation-emission matrix.
Keywords: fluorescence; huminové kyseliny; fluorescence; humic acids